Firearm Injuries to the Wrist and Hand in Children and Adults: An Epidemiologic Study. (June 2023) - Tarkunde, Yash R.; Clohisy, Clayton J.; Calfee, Ryan P.; Halverson, Schuyler J.; Wall, Lindley B.
Background: Gunshot wounds (GSWs) to the wrist and hand are a major health and economic burden in the United States. There are few studies examining the circumstances and epidemiological factors surrounding these injuries. This study assesses the epidemiological factors, as well as the shooting circumstances, injury details, and surgical management of wrist and hand GSWs in children and adults. Methods: Medical records and radiographs were reviewed for all patients with ballistic injury to the wrist or hand treated at an urban academic level 1 trauma center from 2016 to 2019. Fisher exact and Pearson χ 2 tests were used to assess differences between groups. Results: Two hundred forty-nine victims (29 children, 220 adults) with complete documentation were identified. Among 180 victims with known shooting circumstances, 132 (70%) were shot by another person and 110 (65%) were injured by intentional gunfire. Eighty-seven victims (35%) suffered a concurrent GSW to another body region. Metacarpal fracture was the most commonly diagnosed bony injury (37%), followed by proximal phalanx fracture (25%). One hundred twenty-nine victims (52%) underwent surgery following their injuries. Nerve discontinuity was diagnosed in 27 victims (11%), while 20 victims (8%) had vascular disruption. There was no significant difference between children and adult victims' type of fracture, concurrent injuries, rates of surgery, or in the most common fracture fixation method. Conclusions: Most wrist and hand GSW victims were injured due to intentional, non-self-inflicted gunfire. Most patients present with hand fractures, and fortunately, nerve and vascular disruptions are uncommon.